2015
DOI: 10.1038/bjc.2015.321
|View full text |Cite
|
Sign up to set email alerts
|

Pathological responses after angiogenesis or EGFR inhibitors in metastatic colorectal cancer depend on the chemotherapy backbone

Abstract: Background:Optimal preoperative treatment before colorectal cancer metastases (CRCM) resection remains unclear. This study evaluated pathological responses (pR) in CRCM resected after chemotherapy alone or combined with angiogenesis or epidermal growth factor receptor (EGFR) inhibitors.Methods:Pathological response was retrospectively evaluated on 264 resected metastases from 99 patients. The proportion of responding metastases after different preoperative treatments was reported and compared. Patient's progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
5
8
0
1
Order By: Relevance
“…In the present study, the addition of bevacizumab or cetuximab did not result in a significant difference in pathologic response rates for the whole metastases cohort, but these drugs did have an effect when certain chemotherapy backbones were implemented. These results were in agreement with those of most studies that found that the addition of targeted therapy, including bevacizumab and cetuximab, probably has an effect on the pathologic response of colorectal cancer and liver metastases; however, the effect depended on the chemotherapy backbone [ 17 , 25 , 26 , 30 ]. In the present study, for metastases treated with irinotecan-based chemotherapy, the addition of either bevacizumab or cetuximab resulted in higher pathologic response rates than chemotherapy alone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the addition of bevacizumab or cetuximab did not result in a significant difference in pathologic response rates for the whole metastases cohort, but these drugs did have an effect when certain chemotherapy backbones were implemented. These results were in agreement with those of most studies that found that the addition of targeted therapy, including bevacizumab and cetuximab, probably has an effect on the pathologic response of colorectal cancer and liver metastases; however, the effect depended on the chemotherapy backbone [ 17 , 25 , 26 , 30 ]. In the present study, for metastases treated with irinotecan-based chemotherapy, the addition of either bevacizumab or cetuximab resulted in higher pathologic response rates than chemotherapy alone.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, for metastases treated with irinotecan-based chemotherapy, the addition of either bevacizumab or cetuximab resulted in higher pathologic response rates than chemotherapy alone. This confirmed the finding of Carrasco et al [ 25 ] that anti-epidermal growth factor receptor agents combined with irinotecan-based regimens were associated with higher pathologic response rates and further supplemented the advantage of bevacizumab/irinotecan-based regimens. In contrast, for metastases treated with oxaliplatin-based chemotherapy, the addition of bevacizumab led to a pathologic response rate similar to that in the chemotherapy-alone subgroup but led to a higher pathologic response rate than that in the cetuximab-combined chemotherapy subgroup.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Было выявлено, что наи-большая частота выраженных патоморфологических эффектов достигалась при сочетании анти-EGFR антител с иринотекан-содержащими режимами химиотерапии: 55 % против 6 % при комбинациях с оксалиплатином, а также бевацизумаба с оксалиплатин-содержащими схемами: 60 % против 17 % при сочетании с иринотека-ном. Однако следует помнить, что исследование носило ретроспективный характер [18].…”
Section: какой режим химиотерапии лучше комбинировать с таргетным преunclassified
“…Pooling data from these studies estimated that bevacizumab addition increased the occurrence of complete pathologic response by 3.9 %, from 7.8 % with chemotherapy alone to 11.7 % with combined regimen. Although the relevance of the cytotoxic backbone added to preoperative bevacizumab is yet unclear, recent data seem to indicate that the optimization of the associated regimen could impact bevacizumab-induced increase in pathologic response rate [47]. Moreover, bevacizumab had been shown to improve the degree of pathological response [48], and to induce an unusual, infarct-like necrosis [49]; both conditions have been reported to be associated with better prognosis [18].…”
Section: Which Is the Effect Of Bevacizumab On The Pathology Of Livermentioning
confidence: 99%